The role of Financial Mathematics for the development of student skills in High School (Research, Society and Development, 2022)
This paper presents the research results about the exploration of the support material for the State of São Paulo Curriculum (ESPC), authored by the Secretary of Education of the State of São Paulo (SEESP) in collaboration with the teaching community, and used in the Public High Schools in 2020. The support material for ESPC includes the Cadernos: “SP Faz Escola” and “Aprender Sempre”. The investigation aim was to detect the skills that students can develop in the Mathematics and its Technologies area, related to Financial Mathematics and Financial Education, present in the National Common Curricular Base (BNCC). This is a research with a qualitative methodology, of the documentary and bibliographic type, using primary sources, as explained by Cellard for documental research, and we analyze the context of use of the materials, in this case, the Cadernos, identifying the mathematical concepts in action, which is related to Financial Mathematics and, also, the research is bibliographic in agreement with the studies of Lima and Mioto, particularly for the possibility of explaining about the research object offering materiality to the objective of the analysis. As a result, we identified twelve skills distributed among five competencies in the Mathematics and its Technologies area, which provide opportunities for the development and deepening of knowledge objects concerning Financial Mathematics and Financial Education.